2024
DOI: 10.1101/2024.03.14.24304331
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of implementing digital adherence technologies on the use of health care providers’ time and the human resource cost of tuberculosis treatment adherence support in Ethiopia

Mahilet Belachew,
Mamush Sahile,
Demekech Gadissa
et al.

Abstract: Background. The management of human resources for health is a key priority for resource constrained health systems. Digital adherence technologies (DATs) for treatment support offer an opportunity to reorganise existing healthcare worker workload. Historically, tuberculosis treatment services involved directly observed treatment with frequent patient visits to the clinic for treatment adherence support. More recently, digital technologies have offered an option for the digital monitoring of treatment adherence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Differences in provider costs between the SOC and intervention arms of the study were primarily driven by the number of healthfacility visits per treatment episode. In a separate analysis, we showed that health care workers spent more time with PWTB per visit in the intervention arms than when they were attending more frequently in the SOC arm [23]. This increase in time spent remained lower than the cumulative time of multiple visits in the SOC.…”
Section: Discussionmentioning
confidence: 75%
“…Differences in provider costs between the SOC and intervention arms of the study were primarily driven by the number of healthfacility visits per treatment episode. In a separate analysis, we showed that health care workers spent more time with PWTB per visit in the intervention arms than when they were attending more frequently in the SOC arm [23]. This increase in time spent remained lower than the cumulative time of multiple visits in the SOC.…”
Section: Discussionmentioning
confidence: 75%